Systematic Literature Review: Penerapan Virtual dan Augmented Reality dalam Pembelajaran Matematika - Dito, Samuel Benny; Nindiasari, Hepsi; Syamsuri, Syamsuri; Hendrayana, Aan (Griya Journal of Mathematics Education and Application, 2025)
The education sector needs to adapt to the changing times, one of which is through learning technology. There are many types of learning technology, two of which are Augmented Reality (AR) and Virtual Reality (VR). The purpose of this study is to describe the application of virtual and augmented reality in mathematics learning as viewed from the level of education and its influence. A Systematic Literature Review was used in this research method to examine the application of AR and VR in mathematics learning. The results show that AR and VR are used at almost all levels of education, including elementary school, junior high school (SMP), senior high school (SMA), and university. However, they are more commonly used at the junior high school and senior high school levels. The effects of AR and VR include improving learning outcomes, interest, experience, and motivation, critical thinking skills, mathematical spatial skills, visual thinking skills, problem-solving skills, creative thinking skills, and geometric skills.